Improvement in Quality of Life after Septoplasty - Arshad Ullah Afridi, Kunza Ali, Hassan Majid Bhatti, Muhammad Saeed Gohar, Saad Slahuddin, Waseem Ahmad (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Septoplasty is one of the most commonly performed procedures in the ENT department. It is done when a patient presents with a deviated nasal septum, due to which he is not able to live his life to the fullest due to persisting symptoms of congestion, breathing difficulties and recurrent infections etc. It negatively affects his quality of life. In Septoplasty, the deviated nasal septum is removed and the remaining tissue repaired, which should alleviate some of his symptoms. Objective: The objective of this study is to investigate the impact of septoplasty on the symptoms with which a patient first presented due to deviated nasal septum and whether or not their quality of life improved after surgery. Study type, settings and duration: A cross-sectional study was done on the patients who had undergone the procedure of septoplasty in the month of August and September, and a follow-up of their treatment was taken by ENT department on the telephone 1 month later and was documented. Methodology: After the approval of SMDC-IRB, the patients who had undergone Septoplasty in August and September 2021 in Shalamar Hospital were recruited and called upon via a telephone. After obtaining consent, they were asked questions from the self-administered questionnaire regarding the post septoplasty symptoms and the questionnaire itself was duly filled by the ENT department. The response forms were then transported into excel sheets and data was analyzed, response was recorded as percentage and frequency, for demographics, improvements and/or persistence in symptoms and whether they would suggest this procedure to a closed one. Results: This was a cross sectional study with a sample size of 194. According to the analysis there were 46% (n=90) males and 53% (n=104) females in our study. All the study participants were Pakistani nationals. 70% (n=136) underwent septoplasty and 30% (n=58) underwent septoturbinectomy. When asked that will you repeat the same surgical procedure for persistent issue 27% (n=54) said Yes while 72% (n=140) said No. We asked the study participants that will they prefer same surgical procedure for someone they know, 96% (n=187) said yes while 4% (n=7) said no. There was a highly significant (p < .000) difference between perceived symptoms before surgery and after surgery among patients who went for septoplasty and septoturbinectomy. Practical implication: This study signifying the life improvement after septoplasty will entrust the community for a better outcome after the procedure. Evidence based betterment in the life of patients will be encouraging for a more flourishing essence of being. Conclusion: Majority of the people who underwent Septoplasty greatly benefited postoperatively as their symptoms associated with a deviated nasal septum that negatively affected their life before, showed immense improvement and henceforth, their quality of life also ameliorated. Key words; Septoplasty, ENT, Quality, post-procedure, Improvement.